THE MANAGEMENT OF PRIMARY DYSMENORRHOEA (KASHTARTAVA) - A PROSPECTIVE MULTICENTRIC OPEN OBSERVATIONAL STUDY - Sarada, Ota; Kanchnara P, Devi; Madhavi P, Kutty; Krishna, Kumari; Kiran V, Kale; Anu, Bhatnagar; Sushmita Priyadarshini, Ota; Rinku, Tomar; Seema, Jain; Subhashree, M N; Srikanth, N; M M, Padhi; et al. (International Journal of Ayurveda and Pharma Research, 2015)
Objective: To evaluate the clinical usefulness of Rajahpravartini vati in the management of primary dysmenorrhoea (Kashtartava) and changes in the quality of life of the subjects. Study design: A multi-centric prospective single arm observational study. Setting and participants: 359 subjects aged between 16 - 35 years suffering from painful menstruation at least for three consecutive regular menstrual cycles were included in the study. Intervention: Rajahpravartini Vati a classical Ayurvedic formulation was administered 250 mg b.d. with lukewarm water for 90 days followed by subsequent 90 days without intervention. Outcome measures: The management of menstrual pain assessing by 10 points Visual Analogue Scale and improvement in the quality of life using SF-36 (RAND) questionnaire. Results: The mean VAS score of pain at baseline was 6.94±1.98, decreasing to 1.7±2.22 at 90th day which further decreased and maintained to 1.24±1.9 up to 180th day. Associated symptoms like nausea, vomiting, constipation, giddiness, breast tenderness, diarrhea, headache and fainting were completely relieved. The improvements of quality of life in 8 domains viz. pain, general health, physical functioning, social functioning, emotional wellbeing, energy/fatigue, limitation due to physical health and emotional problems at the end of 90th day of intervention was also significant (p<0.001) in comparison to baseline. No adverse event occurred during the treatment period. Conclusion: Rajahpravartini Vati has shown a positive role for the treatment of dysmenorrhoea and to improve the quality of life of the subjects.